China : An Evolving Market Economy; A Review of Reform Experience - Kochhar, Kalpana (IMF Working Papers; Working Paper, 1992)
This paper examines China's reform experience since 1978, reviewing major initiatives taken and assessing their impact on economic structure and their implications for macroeconomic management and stability. It identifies some of the special conditions before and during the reform process that impinged on China's capacity to implement reforms, and, in particular, those where China may differ from other countries undertaking reform, including former CPEs. A further consideration is the choice of the sequence and pace of reform and the structural and institutional changes that are needed to reorient the economy towards the market.